Wrong-way risk in stock swaps: measuring counterparty credit risk and CVA - Ibelli, Rodrigo Trintino (2015)
A stock swap transaction is an alternative way for a company who want to enter into a long position on its own stocks or who intend to set up a repurchase program without having to dispose of cash or contract a loan, or even hedging against increases on its stock prices. In this swap transaction the company receives the return on its own stock, whilst paying a fixed or floating interest rate. However, this kind of swap presents wrong-way risk, that is, a positive dependence between the underlying asset and the counterparty’s default probability, which must be considered by dealers when pricing this kind of swap contracts. In this work we propose a model for incorporating dependence between default probabilities and the counterparty’s exposure in the calculation of the CVA for these kind of swaps. We use a Cox process to model default times, given that the stochastic default intensity follows a CIR model, and assuming that the factor driving the underlying stock price and the factor driving the default intensity are jointly given by a bivariate standard Gaussian distribution. We analyze the impact on CVA of incorporating wrong-way risk in this kind of swap transaction with different counterparties, and for different maturities and dependence levels.